Liquid-liquid equilibria of mixtures with ethyl lactate and various hydrocarbons - Malgorzata E. Zakrzewska (2012)
Mutual miscibility in mixtures containing ethyl lactate and various hydrocarbons (alkanes, alkenes, cyclohexane, alkyl cyclohexanes and terpenes) were explored in a range of temperatures from (273.2 to 320.9) K and at atmospheric pressure. Thus, the respective temperature-composition phase diagrams were constructed. The influence of temperature, aliphatic chain length and of double bond presence on liquid phase behavior was discussed. The obtained liquid-liquid solubility data were represented using the UNIQUAC-based model which showed to be an appropriate tool for representing the liquid-liquid behavior of (hydrocarbon + ethyl lactate) mixtures.